Talent Management Practices on Employee Turnover Intention - Wehelmina Rumawas (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
Human resource managers need to play critical roles to overcome the talented and younger employees' turnover intention in an organization. This study aims to determine the causal relationship between talent management practice, perceived organizational support, and employee engagement and the impact on the turnover intention of Generation Y employees. A convenience sampling technique was used for this research. The study surveyed 182 Generation Y employees. The data collected were initially analyzed using the PLS-SEM method with the smartPLS-3 software. The results showed that talent management practice has a significant effect on perceived organizational support and employee engagement. It is also inferred that talent management practice, perceived organizational support, and employee engagement has a significant negative effect on turnover intention. This study also confirms that perceived organizational support has a significant positive effect on employee engagement. Additionally, this study discovered that perceived organizational support and employee engagement operate as mediators between talent management practices and turnover intention.